2006
DOI: 10.1007/s00432-005-0070-8
|View full text |Cite
|
Sign up to set email alerts
|

Short-term monitoring of cognitive functions before and during the first course of treatment

Abstract: The results suggest that chemotherapy has negative short-term effects on some cognitive functions. But age-dependent effects were only found for memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
0
15
0
2
Order By: Relevance
“…Anecdotal concerns tend to focus on memory and attention problems. The most common areas of cognitive difficulties seen in the BC literature are: working memory, visual memory, verbal memory, executive functioning, information processing speed, attention, learning, and visuospatial functioning [11,27,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal concerns tend to focus on memory and attention problems. The most common areas of cognitive difficulties seen in the BC literature are: working memory, visual memory, verbal memory, executive functioning, information processing speed, attention, learning, and visuospatial functioning [11,27,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…All the other cognitive studies which have measured psychological distress have found no correlation between objective cognitive performance and depression, anxiety and/or mood [11,[13][14][15][16][17]76,78,79,84,85,87,91,119,147]. However, as discussed in Section 6, many studies have found a strong association between perceived cognitive impairment and anxiety and/or depression [11,17,78,87,91,101].…”
Section: Anxiety Depression and Stressmentioning
confidence: 92%
“…The use of a disease specific control group enabled the authors to account for non-chemotherapy disease and host-related factors that might have contributed to cognitive impairment. Also, a study comparing patients tested pre-chemotherapy to a different group tested after their first cycle of chemotherapy showed greater impairment on word generation, memory and verbal learning in the post chemotherapy group, although this finding could be confounded by acute symptoms secondary to the chemotherapy [119].…”
Section: Chemotherapy Studiesmentioning
confidence: 94%
“…Further, the co-morbidities of cancer may include cognitive impairment. Older patients with hematological disease or cancer of the intestinal tract have experienced negative outcomes (Eberhardt Dilger Musial, Wedding, Weiss, & Miltner, 2006). …”
Section: Synthesis Of Researchmentioning
confidence: 99%